Impacts of inter-basin water diversion projects on the feedback loops of water supply–hydropower generation–environment conservation nexus - J. Wang; D. Liu; D. Liu; D. Liu; S. Guo; L. Xiong; P. Liu; H. Chen; J. Chen; J. Yin; J. Yin; Y. Zhang (Hydrology and Earth System Sciences, 2025)
To balance water resource distribution in different areas, inter-basin water diversion projects (IWDPs) have been constructed around the world. Unclear feedback loops of water supply–hydropower generation–environment conservation (SHE) nexus in IWDPs increase the uncertainty in rational scheduling of water resources for water receiving and water donation areas. To address the different impacts of IWDPs on a dynamic SHE nexus and explore synergies, a framework is proposed to identify these impacts across multiple temporal and spatial scales in a reservoir group. The proposed approach was applied to the Hanjiang River Basin (HRB) in China as a case study. Runoff series from the HRB at multiple temporal and spatial scales were provided through the Variable Infiltration Capacity hydrological model. Multi-level ecological flows were determined by the modified Tennant method based on a multi-level habitat condition method. 30 scenarios were set and modeled in a multisource input–output reservoir generalization model. Differences between scenarios were quantified with a response ratio indicator. The results indicate that without IWDPs there is negative feedback between water supply (S) and hydropower generation (H) and between S and environment conservation (E), while there is positive feedback between H and E. The negative feedback of S on H and the positive feedback of E on H are weakened or even broken in abundant-water periods. With IWDPs, water donation basins experience strengthened feedback loops, while water receiving basins experience weakened feedback loops. Feedback loops exhibit intrinsic similarity and stability across different time scales. Feedback loops in reservoirs with a regulation function remain stable under varying inflow conditions and feedback loops for downstream reservoirs are influenced by their upstream reservoirs, especially in low-flow periods. Simply increasing water receiving flow cannot resolve inherent SHE conflicts because of the persistent feedback polarity with IWDPs, and adaptive allocation rules are needed that account for these stable feedback patterns. The proposed approach can help quantify the impacts of IWDPs on SHE nexus and contribute to the sustainable development of SHE nexus.